Assessment of a New E-Learning System on Thorax, Trachea, and Lung Ultrasound. (12th November 2013) - Cuca, Colleen; Scheiermann, Patrick; Hempel, Dorothea; Via, Gabriele; Seibel, Armin; Barth, Magnus; Hirche, Tim O.; Walcher, Felix; Breitkreutz, Raoul
Abstract : Background . Lung ultrasound has become an emerging tool in acute and critical care medicine. Combined theoretical and hands-on training has been required to teach ultrasound diagnostics. Current computer technology allows for display, explanation, and animation of information in a remote-learning environment. Objective . Development and assessment of an e-learning program for lung ultrasound. Methods . An interactive online tutorial was created. A prospective learning success study was conducted with medical students using a multiple-choice test (Trial A). This e-learning program was used as preparation for a certified course followed by an evaluation of trained doctors (Trial B) by linear analogue scales. Pretests were compared with postcourse tests and sustainability tests as well as a posttest of a one-day custom classroom training. Results . In Trial A, during the learning success study (n = 29 ), the increase of correct answers was 11.7 to 17/20 in the post-test and to 16.6/20 in the sustainability test (relative change 45.1%, P < 0.0001 ). E-learning almost equalled scores of classroom-based training regarding gain and retention of factual knowledge. In Trial B, nineteen participating doctors found a 79.5% increase of knowledge (median, 95% CI: 69%; 88%). Conclusion . The basics of lung ultrasound can be taught in a highly effective manner using e-learning.